Reactivation of endogenous retroviral elements via treatment with DNMT- and HDAC-inhibitors. Issue 7 (3rd April 2018) - Daskalakis, Michael; Brocks, David; Sheng, Yi-Hua; Islam, Md Saiful; Ressnerova, Alzbeta; Assenov, Yassen; Milde, Till; Oehme, Ina; Witt, Olaf; Goyal, Ashish; Kühn, Alexander; Hartmann, Mark; et al.
ABSTRACT: Inhibitors of DNA methyltransferases (DNMTis) or histone deacetylases (HDACis) are epigenetic drugs which are investigated since decades. Several have been approved and are applied in the treatment of hematopoietic and lymphatic malignancies, although their mode of action has not been fully understood. Two recent findings improved mechanistic insights: i) activation of human endogenous retroviral elements (HERVs) with concomitant synthesis of double-stranded RNAs (dsRNAs), and ii) massive activation of promoters from long terminal repeats (LTRs) which originated from past HERV invasions. These dsRNAs activate an antiviral response pathway followed by apoptosis. LTR promoter activation leads to synthesis of non-annotated transcripts potentially encoding novel or cryptic proteins. Here, we discuss the current knowledge of the molecular effects exerted by epigenetic drugs with a focus on DNMTis and HDACis. We highlight the role in LTR activation and provide novel data from both in vitro and in vivo epigenetic drug treatment.